Provendo segurança sensível a contexto descentralizada para a industria 4.0 - Portal, Gabriel da Silva Oliveira (2020)
The Internet of Things (IoT) is increasingly being applied to a range of environments, as industry, farming and health. An example is the industry 4.0, that explores concepts as Additive Manufacturing and Cognitive Manufacturing. Such concepts have being presenting major efﬁciency improvements, exploring trend paradigms as Decentralization and Edge computing. However, infrastructure characteristics assecurity were not developed speciﬁc to decentralized approaches. Hence, standard security approaches as cryptography and Software Deﬁned Networks (SDN) has presented security breaches in decentralized and collaborative environments. While such approaches aims to protect a communication layer, decentralized applications can be composed by malicious members, that compromises an application layer. Through threats as Spooﬁng and Tampering, malicious members are able to generate ghost members and data, that can compromise a physical world process. The compromising of a physical world process can cause monetary loses and even put the human life in risk, thus, emerges the need for develop security architectures speciﬁc for decentralized applications. Therefore, this work proposes an architecture that provides an extra security layer to decentralized applications. The Blockchain and the Context-aware Security (CAS) technologies have being showing efﬁcient to respectively provide data integrity and process assertion for IoT. The proposed architecture combines the use of these two technologies, since they have a complementary relationship, providing an improvement in security for decentralized environments. The architecture was validated in an industry 4.0 scenario, more speciﬁcally in an additive manufacturing scenario. The results showed that the architecture was effective for the evaluated cases.